Context-Based Separation of Cell Clusters for the Automatic Biocompatibility Testing of Implant Materials. (20th March 2014) - Buhl, S.; Neumann, B.; Schäfer, S. C.
Abstract : This paper presents a new method to separate cells on microscopic surfaces joined together in cell clusters into individual cells. Important features of this method are that the remaining object geometry is preserved and few contour points are required for finding joints between neighboring cells. There are alternative methods such as morphological operations or the watershed transformation based on the inverse distance transformation but they have certain disadvantages compared to the method presented in this paper. The discussed method contains knowledge-based components in form of a decision function and exchangeable rules to avoid unwanted separations.